A Novel Approach to Fuzzy Soft Set-Based Group Decision-Making. (12th July 2018) - Feng, Qinrong; Guo, Xiao
Abstract : There are many uncertain problems in practical life which need decision-making with soft sets and fuzzy soft sets. The purpose of this paper is to develop an approach to effectively solve the group decision-making problem based on fuzzy soft sets. Firstly, we present an adjustable approach to solve the decision-making problems based on fuzzy soft sets. Then, we introduce knowledge measure and divergence degree based on α -similarity relation to determine the experts' weights. Further, we develop an effective group decision-making approach with unknown experts' weights. Finally, sensitivity analysis about the parameters and comparison analysis with other existing methods are given.